2020
DOI: 10.1364/osac.390604
|View full text |Cite
|
Sign up to set email alerts
|

Atomic line versus lens cavity filters: a comparison of their merits

Abstract: We present a comparison between lens cavity filters and atomic line filters, discussing their relative merits for applications in quantum optics. We describe the design, characterization and stabilization procedure of a lens cavity filter, which consists of a high-reflection coated commercially available plano-convex lens, and compare it to an ultra-narrow atomic band-pass filter utilizing the D 2 absorption line in atomic rubidium vapor. We find that the cavity filter peak transmission frequency and bandwidth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Hence if a large number density [91] is needed, longer cells may be better [92]. The combination of a solenoid and permanent magnets allows us to use a longer cell than in previous oblique investigations [51,70] since the magnitude of the field is largely provided by the permanent magnets while its direction is determined by small adjustments in the solenoid current. This allows easier control of the field magnitude and direction with the permanent magnets set square with the cell resulting in less error in homogeneity.…”
Section: Using An Adapted Version Of the Open-source Software Packagementioning
confidence: 99%
“…Hence if a large number density [91] is needed, longer cells may be better [92]. The combination of a solenoid and permanent magnets allows us to use a longer cell than in previous oblique investigations [51,70] since the magnitude of the field is largely provided by the permanent magnets while its direction is determined by small adjustments in the solenoid current. This allows easier control of the field magnitude and direction with the permanent magnets set square with the cell resulting in less error in homogeneity.…”
Section: Using An Adapted Version Of the Open-source Software Packagementioning
confidence: 99%
“…Most magnetooptical filters rely on thermal vapor cells due to their compact and resilient setups [50]. Thermal vapor filters can be tuned by varying the magnetic field, temperature and input polarization [51,52] and can switch between different D-line operation [53]. It has been shown that by cascading cells, line-center or wing features can be selected [54].…”
Section: Introductionmentioning
confidence: 99%
“…By setting the magnetic field at an oblique angle to the k-vector, the system becomes elliptically birefringent and dichroic [67,68]. While oblique filters have been constructed [51,66,69,70], a treatment on how elliptical birefringence can improve filter performance has not yet been presented. In fact, we show that this elliptical birefringence relies on the eigenmodes of the medium being non-orthogonal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in our atomic plasmonic systems, narrow optical atomic bandpass filters work based on induced transmission in atomic transition lines 17 . These narrow line filters are required in atmospheric LIDAR 18 , laser communication 19 , quantum optics 20 or logic processing which is not possible without dynamic switching 21 .…”
Section: Introductionmentioning
confidence: 99%